Socio-environmental conflict management as a starting point for economic development (Revista Científica Interdisciplinaria Investigación y Saberes, 2021)
The objective of this literature review article is to carry out an analytical observation and determination of fundamental aspects in the field of socio-environmental conflict management and its interaction with the economic development of the people involved, be they communities and/or regions. A detailed review of articles found in different bibliographic registries such as Dialnet, SciELO, Latindex and others has been carried out. We were able to identify 22 articles with topics related to the management of socio-environmental conflicts and their impact on the economic development of the communities involved, which allowed us to analyze relevant information for the development of the article. Upon finding a diversity of literature by authors on the subject, it became evident that an efficient management of socio-environmental conflicts has an impact on the development of the people, which is reflected in a culture of peace. In this line, it was concluded that an efficient interaction of the institutions involved, whether public or private, in the framework of the prevention of socio-environmental conflicts, will bring about sustainable development for the State and its populations